The Effect of maximal Effort Exercises on the Development of Strength Speed and Compound Skill in Trapping, Dribbling and Passing in Futsal for Under 19 years - Ghassy, Abdulkarem; Shamil, Wamed (Journal of Physical Education, 2022)
Maximal effort exercises are considered one of the most important exercises that develop physical and skill abilities in players that futsal players should be trained on especially during matches. The research aimed at identifying the effect of maximal effort exercises on the development of strength – speed and compound skills of trapping, dribbling, and passing. The subjects were Al Seliek club futsal players under 19 divided into two equal groups each group consisted of eight players. The main experiment was applied with two training sessions per week for eight weeks. The results showed that maximal effort exercises have significant effect on the development of strength – speed and compound skills in youth futsal players.